2020
DOI: 10.1590/1678-4766e2020002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of planktonic microcrustaceans (Cladocera and Copepoda) in lentic and lotic environments from the semiarid region in northeastern Brazil

Abstract: Abstract The present study aimed to inventory the biodiversity of planktonic microcrustaceans (Cladocera and Copepoda) in 44 environments from the semiarid region of Brazil, increasing the knowledge about zooplankton community, including phytophilous species. Between 2011 and 2017, organisms were collected in a non - systematic way in the states of Rio Grande do Norte, Pernambuco, Ceará and Paraíba. A total of 60 species of planktonic microcrustaceans were identified, of which 52 were cladocerans and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…1). The narrow distribution of species seems to be well documented as several areas in Brazil were sampled and no specimens of Acantholeberis were mentioned (Sousa & Elmoor-Loureiro 2008, 2012Lansac-Tôha et al 2009;Santos-Winiewski et al 2011;Rocha et al 2011;Brito et al 2020), even those studies performed on the Brazilian coast at latitudes lower than 22° S (Sousa et al 2009;Van Damme & Dumont 2010;Soares & Elmoor-Loureiro 2011;Diniz et al 2020). Thus, A. accolismaris sp.…”
Section: Discussionmentioning
confidence: 99%
“…1). The narrow distribution of species seems to be well documented as several areas in Brazil were sampled and no specimens of Acantholeberis were mentioned (Sousa & Elmoor-Loureiro 2008, 2012Lansac-Tôha et al 2009;Santos-Winiewski et al 2011;Rocha et al 2011;Brito et al 2020), even those studies performed on the Brazilian coast at latitudes lower than 22° S (Sousa et al 2009;Van Damme & Dumont 2010;Soares & Elmoor-Loureiro 2011;Diniz et al 2020). Thus, A. accolismaris sp.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the different types of environment (lentic and lotic) were significantly correlated with the densities of D. lumholtzi . Comparative studies carried out in continental aquatic ecosystems with different flow velocities have demonstrated that there are greater densities and richness of zooplankton species in lentic environments (Diniz et al, 2018; Lansac‐Tôha et al, 2009), such as lakes and reservoirs. Although they make their own movements, the swimming capacity of these organisms is limited, as is the case of D. lumholtzi , which makes them unable to overcome currents and consequently establish or maintain large populations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, we observed that the total of zooplankton species found in our study was lower when compared to other Brazilian regions (Neves et al, 2003, Aoyagui andBonecker, 2004;Eskinazi-Sant'anna et al, 2005;Souza-Soares et al, 2011). However, the species record per region is generally related to the number of specialists researchers in each area, which makes it difficult, or even impossible, to compare results among regions (Silva 2008;Diniz et al, 2020). We know that there is a traditional discrepancy between knowledge about biodiversity in northeastern Brazil when compared to other Brazilian regions, especially from Caatinga biome and semiarid climate (Silva and Perbiche-Neves, 2017;Barros et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are fewer biodiversity studies carried out in the Caatinga when compared to other Brazilian biomes (Silva and Perbiche-Neves, 2017;Barros et al, 2020). The majority of the Caatinga biome has never been investigated or remains sub-sampled (Tabarelli and Vicente, 2004;de Albuquerque et al, 2012), especially for invertebrates groups (Silva and Perbiche-Neves 2017;Diniz et al, 2020). It is also important to note that the Rotifera, Copepoda and Cladocera composition differed between the lakes from Caatinga and the Atlantic Forest biome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation